2021
DOI: 10.1002/art.41528
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tocilizumab for Polyarticular‐Course Juvenile Idiopathic Arthritis in the Open‐Label Two‐Year Extension of a Phase III Trial

Abstract: Objective. To report the 2-year efficacy and safety of tocilizumab (TCZ) in patients with polyarticular-course juvenile idiopathic arthritis (JIA). Methods. Patients ages 2-17 years with active polyarticular-course JIA, in whom treatment with methotrexate was unsuccessful, received 16 weeks of open-label intravenous TCZ in part 1 (once every 4 weeks: 8 mg/kg or 10 mg/kg for body weight [BW] <30 kg; 8 mg/kg for BW ≥30 kg). Assessments were based on the JIA-American College of Rheumatology (ACR) response (define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…As mentioned in several studies, infection is the most frequently revealed side effect of TCZ use [13,23,25]. Contrary to expectations, none of our patients developed TCZ possibly related significant infections.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…As mentioned in several studies, infection is the most frequently revealed side effect of TCZ use [13,23,25]. Contrary to expectations, none of our patients developed TCZ possibly related significant infections.…”
Section: Discussioncontrasting
confidence: 85%
“…Neutropenia is one of the most frequently reported AE in previous reports [8,11,23,25,28] who have reported neutropenia in both sJIA and pJIA in variable frequencies (18%, 50%, 10%, 17%, 37.2%), respectively. In line with the results from previous studies, we reported neutropenia in 3 (5 events) (2 sJIA and one pJIA) (21.4%) patients during the TCZ course.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Patients with dominant IL-6 cytokines have more severe joint disease, and those with dominant IL-18 cytokines are more likely to develop MAS [ 114 ]. As the severity of experimental inflammatory arthritis is greatly suppressed in IL-6 -/- transgenic mice [ 115 ], a promising result was also noted by applying tocilizumab, an IL-6 receptor targeting agent, for the treatment of polyarticular JIA and sJIA [ 116 , 117 ].…”
Section: Effect Of Monocyte/macrophage-produced Cytokines and Chemokinesmentioning
confidence: 99%
“…Therefore, there are increasing opportunities for surgery in patients using molecularly targeted drugs. Tocilizumab, a monoclonal antibody drug against interleukin (IL)-6 receptor, is used for rheumatoid arthritis [ 1 ], Castleman disease, adult Still’s disease [ 2 ] and juvenile idiopathic arthritis [ 3 ]. In addition to these diseases, anti-IL-6 receptor antibodies are anticipated to expand their application as a means of controlling organ damage secondary to cytokine storms generated by the induction of inflammatory responses, and have recently been used for coronavirus disease pneumonia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%